The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/aac.00802-19
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Kelch Propeller Polymorphisms in Clinical Isolates from Ghana from 2007 to 2016

Abstract: The continuous surveillance of polymorphisms in the kelch propeller domain of Plasmodium falciparum from Africa is important for the discovery of the actual markers of artemisinin resistance in the region. The information on the markers is crucial for control strategies involving chemotherapy and chemoprophylaxis for residents and nonimmune travelers to the country. Polymorphisms in the kelch propeller domain of Ghanaian malaria parasites from three different ecological zones at several time periods were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…None of the artemisinin resistance-associated pfk13 mutations observed in Southeast Asia (M476I, Y493H, R539T, I543T, and C580Y) were observed in the sample set. Our study identified the nonsynonymous pfk13 propeller mutations (C532S, S522C, P553T, and Q613H) that have previously been reported to be variants in Africa (28,(44)(45)(46)(47) at low frequencies, as well as some new mutations (Table S5). There were no temporal trends.…”
Section: Resultsmentioning
confidence: 70%
“…None of the artemisinin resistance-associated pfk13 mutations observed in Southeast Asia (M476I, Y493H, R539T, I543T, and C580Y) were observed in the sample set. Our study identified the nonsynonymous pfk13 propeller mutations (C532S, S522C, P553T, and Q613H) that have previously been reported to be variants in Africa (28,(44)(45)(46)(47) at low frequencies, as well as some new mutations (Table S5). There were no temporal trends.…”
Section: Resultsmentioning
confidence: 70%
“…Malaria endemic regions that have previously identified A578S, must enhance surveillance for C580Y allele. Matrevi et al [23] have also detected C580V (very close allele of C580Y) in Central region of Ghana. Furthermore, Feng et al [41] in 2013 also detected three isolates of C580Y SNP in Chinese migrant workers from Ghana.…”
Section: Discussionmentioning
confidence: 92%
“…Kelch 13 A578S allele, as was observed in this study, has also been previously detected in Ghanaian parasite isolates. In Ghana, A578S has been previously identified in three regions, Eastern, Bono (formerly Brong Ahafo) and in the Upper West Regions [23]. The A578S allele is two codons away from C580Y allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the critical pfk13 gene mutation C580Y, which is associated with delayed clearance of ART in Southeast Asia [35,[90][91][92], was not detected across any of the time points. Similarly, the other 8 validated Southeast Asian K13 alleles associated with ART resistance (F446I, N458Y/I, M476I/V, Y493H, R539T, I543T, P553L, R561H), are also rare in Africa [93,94]. The African K13 mutant alleles (including G449A/D, V520A, S522C, C542Y, G544R, G545E, A557S, R561C, A578S, A617V/T, V637A/I/D, G638R) either do not show evidence of selection in the parasite population or have not yet been associated with clinical artemisinin resistance [37,90,94,95].…”
Section: Plos Onementioning
confidence: 99%